Improving High Intellectual Athletes' Decision Making in Open-Skill Sports through Cognitive Training - Priatna, Moch Rizky; Komarudin, Komarudin; Purnamasari, Ira; Novian, Geraldi (Jurnal Patriot, 2025)
Problem: Problems at the level of decision making of athletes in high open-skill sports. Objective: This study aims to examine the effect of cognitive training (life kinetik and brain gym) on decision making in high intellectual athletes. Method: The method used is the experimental method with. The research sample was 21 high intellectual athletes with research instruments using the Advanced Progressive Matrices (APM) test and a decision making test using The Decision Style Questionnaire (DSQ). Results: There is a significant influence of the life kinetik and brain gym training models on the decision making of high intellectual athletes in open-skill sports. In addition, there is no significant difference in the influence between life kinetik and brain gym training on the decision making of high intellectual athletes in open-skill sports. Conclusion: This study concluded that cognitive training using the life kinetik model with the brain gym can increase the decision making level of high intellectual athletes in open-skill sports. Apart from that, the author also provides several suggestions, namely that cognitive training must be carried out appropriately in order to create maximum performance so as to support athletes to excel. So this research is recommended for further research to examine the level of decision making of athletes in open-skill sports.